The Diagnostic Value of Brush Cytology Alone and in Combination with Tumor Markers in Pancreaticobiliary Strictures - Ufuk Barış Kuzu; Bülent Ödemiş; Nesrin Turhan; Erkan Parlak; Selçuk Dişibeyaz; Nuretdin Suna; Erkin Öztaş; Muhammet Yener Akpınar; Adem Aksoy; Serkan Torun; Hakan Yıldız; Ertuğrul Kayaçetin (Gastroenterology Research and Practice)
Aim. Differentiation of malignant and benign strictures constitutes a problem despite the increasing experience of the endoscopists, radiologists, and pathologists. The aim of our study is to determine the factors that affect the efficacy of the ERCP guided brush cytology in PBS and to evaluate its diagnostic success when used alone and together with tumor markers. Method. The data from brush cytologies of 301 PBS patients were collected retrospectively and analyzed. The final diagnosis was approved based on the histological examination of the tissue taken surgically or by other methods. In the absence of a histological diagnosis, the final diagnosis was based on radiological studies or the results of a 12-month clinical follow up. Results. A total of 28 patients were excluded from the study. From the remaining 273 patients 299 samples were analyzed. The sensitivity and the specificity of brush cytology in diagnosing malignancy are 62.4% and 97.7, respectively. The sensitivity of brush cytology increased to 94.1% when combined with CA-19.9 and CA-125. Conclusion. Brush cytology is a useful method in diagnosing pancreaticobiliary strictures. Advanced age, stricture dilatation before sampling, the presence of a mass identified by radiological studies, high levels of CA-19.9, ALT, and total bilirubin increase the sensitivity of brush cytology.